Development of dissolved oxygen control system for indoor prawn culture - Shaari, Muhammad Farid (2006)
Prawn farming industry is now evolving to intensive and super intensive system. Both systems require more automation than traditional methods for a better prawn production management. Automation helps to increase the profits and revenues as well. Waste, such as cycle time and redundant energy could be decreased to the minimum level. Water quality control is one of the vital factors in prawn production which needs automated system. In this research, dissolved oxygen as one of the influential parameters in water quality control had been focused. A system was designed to sustain the dissolved oxygen concentration in prawn culture tank automatically. This system responded to the concentration in real time and activated the aeration process to increase the dissolved oxygen concentration to the set limit. Five tests were executed to ensure this system is reliable and reasonable to be used. It consists of functionality test, variables tests, energy consumption test and aeration efficiency test. The results showed that it can operate well and less energy consumed compared to typical aeration practice. However, the aeration efficiency was quite good because of the aerator's design. Solutions and suggestions was drafted for a better system performance.